Synchronous Microscopic Epstein-Barr Virus–Positive Diffuse Large B-Cell Lymphoma of the Adrenal and Lymphoplasmacytic Lymphoma: De Novo Disease or Transformation?. (June 2017) - Moonim, Mufaddal T.; Nasir, Alia; Hubbard, Jonathan; Ketley, Nicholas; Fields, Paul
Lymphomas arising in the adrenal are rare, and to our knowledge, 2 cases of Epstein-Barr virus (EBV)–positive diffuse large B-cell lymphomas (DLBCL) in an adrenal pseudocyst have been reported. We report an incidental EBV-positive DLBCL arising in an adrenal pseudocyst in a 58-year-old man with a 7-year history of lymphoplasmacytic lymphoma (LPL). The DLBCL was present in the fibrinous exudate, while the LPL resided in the cyst wall. The patient underwent de-roofing of the same cyst 3 years previously; review of histology revealed foci of LPL in the cyst wall, but not of DLBCL. There have been reports of similar microscopic EBV-positive DLBCLs within enclosed cystic spaces. However, all these cases were incidental extranodal primary DLBCLs. Since residual LPL was present alongside DLBCL, with similar light chain restriction, we propose that this may represent transformation, rather than a de novo primary EBV-driven lymphoma.